2010
DOI: 10.4088/jcp.08m04724gry
|View full text |Cite
|
Sign up to set email alerts
|

Depression Predicts Cognitive Disorders in Older Primary Care Patients

Abstract: Depressive disorders pose increased risk of incident dementia or cognitive disorder NOS in older primary care patients. Clinicians treating depressed older adults should monitor for development of cognitive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
0
17
2
1
Order By: Relevance
“…This activity restriction may manifest as depression 1720. Depression is thought to increase the likelihood of cognitive decline 10,11,47. However, caution should be used while prescribing antidepressants to patients who have fallen as studies have shown that these medications cause an increased risk in falling equal to that of untreated depression 16,48.…”
Section: Discussionmentioning
confidence: 99%
“…This activity restriction may manifest as depression 1720. Depression is thought to increase the likelihood of cognitive decline 10,11,47. However, caution should be used while prescribing antidepressants to patients who have fallen as studies have shown that these medications cause an increased risk in falling equal to that of untreated depression 16,48.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms include cognitive impairment and loss of memory, implicating synaptic dysfunction in the pathophysiology of MDD 46 . This possibility is supported by studies demonstrating a reduction of dendritic spine number and function of neurons in PFC in animal models of depression 7,8 .…”
mentioning
confidence: 99%
“…62 Depressed adults with executive dysfunction have a greater risk for relapse, are less responsive to pharmacologic interventions, and have poorer functional status. 63-65 Because late-life depression is associated with persisting cognitive impairment 8 and may be a sign of prodromal dementia, 66 prevention and early treatment of both vascular conditions and depression are important. Treating modifiable risk factors, such as hypertension, hyperlipidemia, obesity, and diabetes, and implementing health behaviors, such as increasing exercise, are key primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%